THE EFFECT OF FINANCIAL PERFORMANCE ON THE QUALITY OF SUSTAINABILITY REPORTS WITH ENVIRONMENTAL UNCERTAINTY AS A MODERATING VARIABLE - Mahesti Pramusinta; Sri Hastuti; Januar Eko Prasetio (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The purpose of this research is to determine the effect of financial performance on the quality of sustainability reports and to identify the moderating variable of environmental uncertainty that moderates financial performance on the quality of sustainability reports. Population of this research use sector energy which listed in IDX from 2022 until 2024 period which use purposive sampling methods with simple regression linear analysis and moderating regression analysis. Research results show that financial performance has a positive effect on the quality of sustainability reports, and that environmental uncertainty can moderate the effect of financial performance on the quality of sustainability reports. The theoretical implications of this study can serve as a reference for future research on the same topic. The practical implication is that companies can improve their financial performance in order to enhance the quality of their sustainability reports.